Ethiopia Alive & Thrive Process Evaluation Survey 2013: Supervisors of Health Extension Workers - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
This dataset is the result of the supervisors of health extension workers survey that was conducted to gather data for the process evaluation part of the impact evaluation of the Alive & Thrive (A&T) interventions in Ethiopia. The broad objective of the impact evaluation in Ethiopia is to measure the impact of A&T’s community-based interventions (CBI), delivered through the government's health extension program (HEP) platform, in the reduction of stunting and improvement of infant and young child feeding (IYCF) practices in two regions where the integrated family health program (IFHP) operates, namely Tigray and SNNPR (Southern Nations, Nationalities, and People’s Region). A&T is a six-year initiative funded by the Bill & Melinda Gates Foundation to facilitate change for improved infant and young child feeding (IYCF) practices at scale in Bangladesh, Ethiopia, and Viet Nam. The goal of A&T is to reduce avoidable death and disability due to suboptimal IYCF in the developing world by increasing exclusive breastfeeding (EBF) until 6 months of age and reducing stunting of children 0-24 months of age. The process evaluation (PE) is intended to answer one of the major learning objectives for the overall initiative, i.e., how A&T interventions achieve their impact. In Ethiopia, the studies that have been conducted as part of the process evaluation include: 1) a case study in 2011 to explore the extent of the training rollout among frontline health workers (FHWs) and to assess FHW and household exposure to interpersonal communication (IPC) tools developed by A&T, 2) a qualitative study in 2012 that included in-depth interviews with health extension workers (HEWs), HEW supervisors, and volunteers and shorter interviews with mothers and fathers to understand modalities of service delivery under IFHP and other A&T platforms, and 3) a quantitative survey in 2013 among FHWs and households to assess different aspects of service delivery and exposure to A&T community based program interventions. The Ethiopia process evaluation surveys of frontline health workers and households had two broad objectives. The first objective was to assess and understand the FHW work environment related to IYCF service delivery, in order to better answer how A&T interventions achieve impact. The second objective was to assess households’ exposure to the A&T program components/activities, as well as to compare IYCF knowledge and practices to the baseline survey in 2010 in order to get an idea of progress toward impact. Three types of FHW questionnaires (HEW, VCHP, and supervisors) applied to health staff who are closest to the community or work in the community. These questionnaires were aimed at assessing four major issues: 1) FHW’s exposure to training and IPC tools provided by the A&T program, 2) FHW’s exposure to the A&T multi-media components (radio and television messages), 3) FHW’s knowledge and understanding of IYCF and nutrition, 4) the FHW work environment related to IYCF service delivery (motivation, supportive supervision, time commitments to different tasks, and the ability to integrate sustained IYCF counseling into daily routines). The roles of the supervisors are somewhat different from the other two types of health staff. They do not come in direct contact with caregivers, yet they are mainly responsible for providing training to the HEWs and monitoring and supervising the training of volunteers, conducted by the HEWs. The questionnaire for supervisors, therefore, aims at capturing these interactions.